Postcombustion carbon dioxide gas conversion to methanol and dimethyl ether - Tyagi P.; Kapur M.; Kumar V. (My University, 2025)
Carbon dioxide (CO2) conversion to methanol and dimethyl ether (DME) is a rapidly developing technology that has the potential to make significant contributions toward mitigating climate change and achieving a sustainable carbon-neutral environment. These technologies aim to reduce and reuse CO2 emissions to produce valuable fuels for applications in energy production, transportation heating, etc. One of the most significant advantages of postcombustion CO2 conversion to liquid fuels is that it can utilize CO2 emissions from sources, such as fossil, coal-based power plants and natural gas plants, refineries, steel, and fertilizer production units. The CO2 conversion can be integrated in existing industrial processes, helping to reduce CO2 emissions from multiple sectors. To reduce the dependency on fossil fuels, methanol and DME may either be utilized as a clean-burning fuel or as a feedstock for the synthesis of other important chemicals such as formaldehyde, olefines, and DMC. Despite their promising potential, the development of processes for postcombustion CO2 conversion to methanol and DME faces several challenges related to efficiency, catalyst, scalability, and cost-effectiveness of integration with other industrial processes. This chapter is aiming to provide a comprehensive overview of the different pathways for CO2 conversion to methanol and DME, reaction mechanism, and the type of catalysts involved in conversion of CO2 to methanol and DME. In addition to the environmental impacts and sustainability, including present status and future possibilities, the challenges and limitations associated with various CO2 conversion technologies are addressed. © 2025 Elsevier Inc. All rights reserved.